GEOLOGICAL AND MINING EDUCATION TASKS CONSIDERING NEW FACTORS OF ECONOMIC GROWTH IN RUSSIA - V. I. Lisov; O. S. Bryukhovetskiy (Известия высших учебных заведений: Геология и разведка)
The paper considers the main tasks of the state and perspectives of the development of the engineering geological education and increasing its quality, which were discussed at the round table «Competitiveness of the education. Geological education: problems and perspectives», carried out during the 13th International exhibition «Nedra 2016: Studying. Prospecting. Production». One of the actual problems is a lack of budget financing of the resource universities, which lowers the competitiveness of our specialists on the international labor market, which leads to the deformation of the educational system itself, which is for the preparation of the qualified professionals in mineral-source sector of economics.